PENGEMBANGAN MEDIA SCRABBLE UNTUK MENDUKUNG KETERAMPILAN BERBICARA BAHASA JAWA KRAMA SISWA KELAS 5 SD NEGERI 2 PETIR BANTUL - Febriawati, Ulfie Fajri; Arikunto, Suharsimi (universitas Ahmad Dahlan, 2018)
This study aims to develop Javanese learning media for Krama Language material to support speaking skills that can help teachers deliver the material. This research is a research and development (R&D) using the 4D (four-D) development model. This research was conducted on fifth-grade students at SD Negeri 2 Petir Bantul. The product trial subjects are six students, and the trial run is 18 students. This study used instruments in the form of questionnaires and oral tests. The analysis of this research is qualitative and quantitative analysis. The results of the study from expert validation got an average value of 88.76 (Very Good). Product trials were obtained from the responses of teachers and students with grades of 96.88 (Very Good) and 93.33 (Very Good). Students' oral test scores before using the media are 60 (good); then, after using get a value of 95 (Very Good) trial use of the response of teachers and students get a value of 96.63 (Very Good); and 96.97 (Very Good). The oral test of students before using the media is 48.89 (less); after using get a value of 86.11 (Very Good). Overall, data from all assessments of the quality and feasibility of Kramaic Scrabble media are included in the category of Very Good (SB).